Paciente de sexo masculino de 64 años de edad con diabetes mellitus tipo ii e hipertensión arterial y presenta sobrepeso. - Fuentes Briones, Mayron Tomas (2020)
In this case, a 64-year-old male patient presenting with type 2 diabetes mellitus, high blood pressure, and overweight is presented, in this clinical case the biochemical, anthropometry, clinical and dietary values were evaluated, for which they were performed dietary recommendations, the respective caloric calculation was performed giving results of the calories that the patient should consume, since apparently in his BMI because of the overweight that the patient evidences he was ingesting an excess of calories, with this the respective recommendation was made taking into account their present pathologies. The clinical case has as main objective: To determine the nutritional needs according to each patient's pathology, therefore the nutritional status of the patient is evaluated, the nutritional plan is made based on caloric requirements, carbohydrates, lipids and proteins with its due percentage of adequacy. Lifestyle modifications offer the potential to prevent hypertension, are effective in lowering blood pressure and can reduce other cardiovascular risk factors at a low cost and with minimal risk. Patients should be aggressively stimulated to adopt these lifestyle modifications, particularly if they have additional risk factors such as diabetes mellitus. Although lifestyle modifications alone are not adequate to control hypertension, they can reduce the number and dose of antihypertensive medications necessary for the management of this condition (Araya Orozco, 2004).